Pengembangan Website Deteksi Minat Karir Berdasarkan Teori Karir John Holland - nararya rahadyan budiyono; Adam Sekti Aji (JURNAL KONSELING GUSJIGANG, 2020)
Career maturity begins with good planning and self-understanding of career decision making variables. The survey shows the high rate of individual unpreparedness in terms of planning and related self-understanding. The availability of media and instrumentation developed from the results of research that able to accommodate the identification of career types and recommendations is still limited. This becomes the basis for researchers to develop and produce information innovation products and career assessments based on John Holland's theory in the form of a website. The research was conducted using the RnD method involving 2 media experts and 3 material experts. The results showed that the products developed were in the Appropriate and Very Appropriate categories for use. Furthermore, a survey of respondents regarding the appropriateness of the assessment results with individual conditions shows the appropriate and very suitable categories. It can be concluded that the innovation product developed is suitable for use as a media and career type assessment instrumentation.